Liver Enzymes as Surrogate Markers of Hepatitis C Histopathology – Avoiding the Liver Biopsy Needle? - Stephen GM Wong; Eric M Yoshida (Canadian Journal of Gastroenterology)
A retrospective cohort study of 79 patients with chronic hepatitis C was performed to assess the predictive nature of various variables (age, sex, route of transmission, extent of steatosis, alcohol consumption and serum aminotransferase values), with the underlying hepatic histopathology. The newly modified Knodell histological activity index by Desmet et al (1), which separately scores the inflammation from the fibrosis on the liver biopsy, was used. Using stepwise multivariate logistic regression, it was discovered that serum aspartate aminotransferase (AST) values had a predictive relationship with overall histological activity (r=0.62), portal inflammation (r=0.58), piecemeal necrosis (r=0.61) and extent of hepatic fibrosis (r=0.64). Serum AST values correctly predicted the inflammatory grade in 63 of 79 (80%) patients, and the fibrosis stage in 50 of 79 (63%) patients - higher than the predictive values of ALT. Serum alanine aminotransferase (ALT) values did not correlate with the degree of histological inflammation (r=0.39) but did correlate mildly with the extent of hepatic fibrosis (r=0.51). There were no significant correlations of the other variables with histological inflammation or fibrosis.